Recurrent odontogenic keratocyst and the use of Carnoy’s solution: a case report - Henriques, João Cesar Guimaraes; Silva, Keren Quaiatti da; Paula, Cristiane Angélica de Paiva; Lima, Livia Bonjardim; Paulo, Luiz Fernando Barbosa de; Faria, Paulo Rogerio de (Brazilian Dental Science, 2024)
Background: Odontogenic keratocyst is a challenging odontogenic lesion, originating from the epithelial remnants of the dental lamina, ranging from small cysts to extensive lesions with a high recurrence rate and morbidity for patients. The sometimes aggressive nature of these pathological entities explains the controversy among researchers regarding the best classification for these lesions, justifying the fact that these odontogenic cysts were once defined as benign odontogenic tumors for some years. However, there is consensus among scholars that it is a disease that requires careful follow-up of affected patients due to the high recurrence rates, especially in the first two decades after treatment completion. Objectives: The present study aims to elucidate the case of a patient with a mandibular odontogenic keratocyst who prematurely discontinued follow-ups and had a significant recurrence of the lesion after 7 years. Description: the second treatment was performed using Carnoy’s solution. Conclusion: Carnoy’s solution is an absolutely essential therapeutic resource in the treatment of odontogenic keratocysts, as its use significantly reduces the potential recurrence of the disease. KEYWORDS Decompression; Odontogenic cysts; Odontogenic keratocyst and mandible; Odontogenic tumor; Recurrences.